Simulating Planetary Dynamics in a Laboratory Setting. (9th April 2013) - Kumar, Mohi
Abstract : The technological feats of rovers on planets and the stunning images that these and other space missions return from celestial bodies in the solar system tend to dominate public perception of what it means to be a planetary scientist. However, many planetary scientists are also involved with experimental planetary science research in the laboratory.